Pengembangan Sistem Manajemen Layanan Jasa Servis Alat Elektronik Rumah Tangga (Studi Kasus: UKM Bali Tekindo Jaya) - Ni Luh Irma Arini; Bayu Priyambadha; Heru Nurwarsito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
UKM Bali Tekindo Jaya is one of the small and medium-sized businesses that offers repair and installation services in electronic appliances such as air conditioners, refrigerators, rice cookers, washing machines, water heaters, and so on. In running a business, improving the quality of service to customers certainly needs to be supported by good and effective business management so that a management system is needed that can help maximize business services in Bali Tekindo Jaya SMEs. To help manage the business management of Bali Tekindo Jaya SMEs, this document discusses the development of a website-based management system that uses the CodeIgniter framework with php languages ​​and MySQL as the database. This system focuses on business management equipped with booking service features, agendas, reports, assessments, testimonials, and notifications using the SMS Gateway. The test results carried out by the black box and white box method on the website show that all functional systems can be run properly, which is valid in all test cases. The systems usability shows that the system satisfying user also the systems compatibility testing carried out on various web browsers shows that the management system that has been developed does not have significant problems when run on various browsers.